PENGARUH KEPEMIMPINAN TRANSFORMATIONAL DAN DUKUNGAN ORGANISASI TERHADAP KREATIVITAS KARYAWAN MELALUI BERBAGI PENGETAHUAN SEBAGAI VARIABEL MEDIASI - Dezar, Salsabila; Yuniawan, Ahyar (Diponegoro Journal of Management, 2023)
ABSTRACT Today's tough competition and dynamic environment have forced companies to rethink the way they manage to get the best out of their employees. One way that companies can do this is by developing the creativity of their employees. With this, the company can get the best ideas from employees. Activities that can be carried out to influence the level of employee creativity include leadership styles, organizational support, and knowledge sharing. The population in this study were employees of BSI Region VII or the Semarang region. The sampling technique in this study used a census where all members of the population were used as samples from various employees with different positions. The analysis technique used is path analysis with the SPSS 25 program to determine the path coefficient and the effect of the independent variables on the dependent variable. This study aims to examine the effect of Transformational Leadership and Employee Creativity on Employee Creativity mediated by Knowledge Sharing on employees of PT Bank Syariah Semarang. The results of the study show that Transformational Leadership has a positive and significant effect on Employee Creativity. Transformational Leadership has a positive and significant effect on Knowledge Sharing. Organizational Support has a positive and significant effect on Employee Creativity. Organizational Support has a negative and insignificant effect on Employee Creativity.